The Relationship between Credibility and Influencer Attractiveness to Company Brand Trust (A Study on the Relationship between Korean Reomit Influencers and Public Trust in PT. Bank Negara Indonesia Persero, Tbk.) - Purnomo, Candy Bestari (Indonesian Journal of Multidisciplinary Science, 2025)
The rise of Millennials and Generation Z as active economic participants in Indonesia has compelled banks to develop strategies to attract these segments. One effective approach is the use of social media influencers, who are widely followed, credible, and cost-effective. BNI, recognizing this trend, collaborated with Korea Reomit, an influencer based in Seoul with a predominantly Indonesian audience, to promote its South Korea branch. Despite the growing use of influencers in marketing, limited empirical evidence exists regarding how influencer attributes, such as credibility and attractiveness, affect consumer trust in banking brands. This study aims to examine the relationship between influencer credibility and attractiveness and brand trust among Millennial and Gen Z consumers. A quantitative methodology was employed using a non-probability convenience sampling technique. Data were collected from 120 participants aged 18–35 who had viewed Korea Reomit's promotional video about BNI. The results indicate that both source credibility and source attractiveness have a significant positive effect on brand trust. These findings suggest that carefully selected influencers with high credibility and appealing characteristics can effectively enhance consumer trust in banking brands. The study provides practical implications for financial institutions seeking to leverage influencer marketing to engage younger audiences, as well as theoretical contributions to understanding the dynamics of influencer attributes in brand trust formation.